a) 3x (25x + 15) – 35 (5x + 3) = 0 b) (2 – 3x)(x + 11) = (3x – 2)(2 – 5x)

a) 3x (25x + 15) – 35 (5x + 3) = 0

b) (2 – 3x)(x + 11) = (3x – 2)(2 – 5x)

2 bình luận về “a) 3x (25x + 15) – 35 (5x + 3) = 0 b) (2 – 3x)(x + 11) = (3x – 2)(2 – 5x)”

  1. b) 3x(25x+15) -35(5x+3) =0
    =>75x^2-130x-105=0
    =>5(3x-7) (5x+3) =0
    =>\(\left[ \begin{array}{l}3x-7=0\\5x+3=0\end{array} \right.\) 
    => \(\left[ \begin{array}{l}x=\dfrac{7}{3}\\x=-\dfrac{3}{5}\end{array} \right.\) 
    Vậy x=7/3;x=-3/5
    $\\$
    b) (2x-3x) (x+11) =(3x-2) (2-5x)
    =>(2-3x) (x+11) -(3x-2) (2-5x) =0
    =>12x^2-47x+36=0
    =>(3x-2) (4x-13) =0
    =>\(\left[ \begin{array}{l}3x-2=0\\4x-3=0\end{array} \right.\) 
    => \(\left[ \begin{array}{l}x=\dfrac{2}{3}\\x=\dfrac{13}{4}\end{array} \right.\) 
    Vậy x=2/3;x=13/4

    Trả lời
  2. a) 3x (25x + 15) – 35 (5x + 3) = 0
    ⇔ 15x(5x + 3 ) – 35 (5x+3) =0 
    ⇔ (5x + 3) (15x -35)=0 
    ⇒ 5x + 3= 0 hay 15x -35 =0
    ⇒ 5x = 0 -3           15x = 0 +35
    ⇒ 5x = -3              15x = 35
    ⇒ x = -3/5               x = 35 /15
    ⇒   x =-3/5                            x = 7/3
    b) (2 – 3x) (x + 11) = (3x – 2)(2 – 5x)
    ⇔  (2-3x) (x+11)-(3x-2) (2-5x)=0
    ⇔  (2-3x) (x+11)+(2-3x) (2-5x)=0
    ⇔  (2-3x) (x+11+2-5x)=0
    ⇔  (2-3x)(-4x+13)=0
    ⇒  2-3x=0 hay -4x+13=0
    ⇒ 3x = 2-0           -4x = 0 -14
    ⇒ 3x = 2               -4x = -14
    ⇒  x = 2/3              x = -14/-4
    ⇒ x = 2/3               x = -7/-2  

    Trả lời

Viết một bình luận

Câu hỏi mới